The effectiveness of Lactobacillus reuteri on serum bilirubin levels in neonatal hyperbilirubinemia with phototherapy - Deska Andina Rezki; Isra Firmansyah; Dora Darussalam; Sulaiman Yusuf; Nora Sovira; Bakhtiar Bakhtiar (Indonesian Pediatric Society, 2023)
Background Hyperbilirubinemia occurs in 60% of full term and 80% of premature infants. Phototherapy is the main treatment, but it has side effects, sometimes requires hospitalization, and causes the baby to be separated from the mother. Underdeveloped gut microflora and increased enterohepatic circulation in newborns contribute to increased serum bilirubin levels in early life. Objective To assess the efficacy of adding probiotic L. reuteri on phototherapy in full-term neonates with hyperbilirubinemia. Methods In this double-blind, randomized clinical trial, full term infants with hyperbilirubinemia at Dr. Zainoel Abidin Hospital, Banda Aceh, Aceh, Indonesia, were randomly assigned to either an intervention or control group. All subjects received phototherapy. The intervention group was also given five drops of L. reuteri once a day orally before phototherapy started, while the control group received a placebo. Bilirubin levels after 24-hour phototherapy were evaluated in both groups. Results A total of 42 term neonates met the inclusion criteria. The intervention group had a significantly greater decrease in total serum bilirubin (TSB) level (6,517 mg/dL) than did the control group (4,434 mg/dL) (P<0.001), as well in indirect bilirubin levels in the intervention group had decrease 6.40 mg/dL while in the control group 4.43 mg/dL after 24 hours of phototherapy (P<0.001). Conclusion In full-term neonates with hyperbilirubinemia who underwent 24-hour phototherapy, adding probiotic L. reuteri leads to a significantly greater reduction in total and indirect bilirubin levels compared to the control group.